Application of Kirkpatrick Model to Measure Employee Agility to Employee Performance of PT Telkom Indonesia - Dinda Aulia Rahmah; Arry Widodo; Anita Silvianita; Nurafni Rubiyanti (Formosa Journal of Multidisciplinary Research, 2024)
This study aims to determine the relationship between Reaction, Learning, Behavior, Result, Employee Agility, and Employee Performance using AfRAM (Agility for B2B Regional &; Account Management Team) trainee data. In this study using proportional sampling technique. In analyzing the data collected using PLS-SEM. The result of the study is that employee agility is an urgency and the company's needs continue to increase. Agility benefits employee performance. Employee Agility can be developed through training. Research evaluation is very important to measure the success rate of training, the evaluation method used is kirkpatrick. Employees with a high level of agility can implement the skills learned in training effectively, demonstrating a strong relationship between training and employee performance.